2005
DOI: 10.1111/j.1348-0421.2005.tb03630.x
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica Serovar O:8 Infection in Breeding Monkeys in Japan

Abstract: In the period from December 2002 to January 2003, 5 of 50 squirrel monkeys (Saimiri sciureus) housed at a Zoological Garden in the Kanto region of Japan died following a few days' history of diarrhea. After this outbreak had ended in the squirrel monkeys, 1 of 2 dark-handed gibbons (Hylobates agilis) died in April of 2003, showing similar clinical signs. We examined the organs of 3 of the dead squirrel monkeys and of the dark-handed gibbon, and Yersinia enterocolitica serovar O:8, which is the most pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Indistinguishable genotypes have been found among strains isolated from humans and wild rodents, and small rodents are considered responsible for human infections and outbreaks in monkeys in Japan (42,43). In one single study, employing an experimental oral pig model, a conventional large breed was used to assess the pathogenic potential of a restriction-deficient (R Ϫ M ϩ ) derivative of strain O:8 8081v.…”
Section: Discussionmentioning
confidence: 99%
“…Indistinguishable genotypes have been found among strains isolated from humans and wild rodents, and small rodents are considered responsible for human infections and outbreaks in monkeys in Japan (42,43). In one single study, employing an experimental oral pig model, a conventional large breed was used to assess the pathogenic potential of a restriction-deficient (R Ϫ M ϩ ) derivative of strain O:8 8081v.…”
Section: Discussionmentioning
confidence: 99%
“…Indistinguishable genotypes were found among strains isolated from humans, wild rodents and pigs, indicating that wild rodents and pigs are possible infection sources for human Y. enterocolitica O:8 infections. Iwata et al (2005) recently reported the first fatal cases of Y. enterocolitica O:8 infection in monkeys. Using PFGE, ribotyping and REAP, they demonstrated that the genotypes of almost all outbreak isolates were undistinguishable from each other, indicating a common infection source.…”
Section: Epidemiology Of Y Enterocoliticamentioning
confidence: 99%
“…They found that all 38 strains of serotype O:5,27 possessed inv, ail , and ys t genes, suggesting that untreated water may be responsible for the human infection with Y. enterocolitica . In another study, Y. enterocolitica O:8 strains have been isolated from stream water in Japan, which indicate that stream water may be a possible infection source for human Y. enterocolitica O:8 infections [84, 123]. …”
Section: Epidemiological Studies and Outbreaksmentioning
confidence: 99%